2019
DOI: 10.1088/1361-6560/ab1758
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel 3D printed patient specific phantom for quality assurance in cranial stereotactic radiosurgery applications

Abstract: In single-isocenter stereotactic radiosurgery/radiotherapy (SRS/SRT) intracranial applications, multiple targets are being treated concurrently, often involving non-coplanar arcs, small photon beams and steep dose gradients. In search for more rigorous quality assurance protocols, this work presents and evaluates a novel methodology for patient-specific pre-treatment plan verification, utilizing 3D printing technology. In a patient’s planning CT scan, the external contour and bone structures were segmented and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 52 publications
0
36
0
5
Order By: Relevance
“…The results showed a dramatically reduced passing rate at 2%/1 mm in all scenarios. This is attributed to the uncertainty of the film dosimetry protocol, as Makris et al reported the film‐to‐CT image registration uncertainty to be in the order of 1.5 mm 16,22 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed a dramatically reduced passing rate at 2%/1 mm in all scenarios. This is attributed to the uncertainty of the film dosimetry protocol, as Makris et al reported the film‐to‐CT image registration uncertainty to be in the order of 1.5 mm 16,22 …”
Section: Resultsmentioning
confidence: 99%
“…The film was calibrated using a single‐channel protocol with the red color channel 15 . The irradiated films were digitized with an EPSON flat‐bed color scanner (Perfection V850 Pro, Nagano, Japan) using the scanning parameters described by Makris et al 16 After the film scans, the net optical density values were converted into the absolute dose values. The spatial resolution of the film was 0.169 mm.…”
Section: Methodsmentioning
confidence: 99%
“…The primary advantage of gel dosimetry in an anthropomorphic phantom is that, unlike other patient-specific QA, it does not rely on a recalculation of the plan on a phantom nor on the process with which to reconstruct a 3D dose distribution. Rather, the measurement in this phantom can be directly compared with the patient's calculated dose distribution as was demonstrated by Makris et al 13 . Finally, for the most realistic execution of an end-to-end test, an anthropomorphic phantom is the best substitute to approximate the entire process.…”
Section: Phantom Designmentioning
confidence: 99%
“…A combined 1σ dosimetric uncertainty of 2.3% was estimated for the dose level of 8 Gy which was the prescription dose. According to Pappas et al (2017) 16 study, a spatial 1σ uncertainty of 1.5 mm is resulting from the spatial registration procedure between scanned film images and the CT dataset of the film phantom following a registration technique described elsewhere 13,16 .…”
Section: Film Dosimetry and Uncertaintymentioning
confidence: 99%
“…Recent dispersion of low-cost three-dimensional (3D)-printing technology has allowed for the development of (patient) specific phantoms in radiotherapy. [6][7][8] This work describes the development of a series of end-to-end left breast attachments to the CIRS SBRT thorax phantom, using a mid-range 3D printer, allowing for commissioning of breast radiotherapy treatment techniques. All phantoms are fully compatible with surface scanning technology for accurate positioning and have either a film or IC insert centrally located in the breast.…”
Section: Introductionmentioning
confidence: 99%